2022
DOI: 10.1002/smll.202106395
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Silicon‐Doped Polyether Network for Double Stable Interfaces in Quasi‐Solid‐State Lithium Metal Batteries

Abstract: are difficult to be simultaneously compatible with Li metal anode with a strong reducibility and metal-oxide cathode with high oxidizability. [9][10][11] The most effective strategy to solve the above-mentioned problems is the formation of stable solidelectrolyte-interface (SEI) layer between electrolyte and anode/cathode. [12][13][14] Therefore, the development of polymer-based QSE that can form the stable SEI layers on anode and cathode have great potential to improve the cyclic stability and safety of Li-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…[1] The detrimental oxygen release upon repeated cycling would induce irreversible structural transformation and fast capacity fading as well as severe safety concerns. [26] The results herein clearly confirmed that the LBO modification could stabilize the lattice O in Ni-rich cathode, consistent with the above-mentioned theoretical calculations (Figure 1b-e).…”
Section: Resultssupporting
confidence: 91%
“…[1] The detrimental oxygen release upon repeated cycling would induce irreversible structural transformation and fast capacity fading as well as severe safety concerns. [26] The results herein clearly confirmed that the LBO modification could stabilize the lattice O in Ni-rich cathode, consistent with the above-mentioned theoretical calculations (Figure 1b-e).…”
Section: Resultssupporting
confidence: 91%
“…In accordance with this point, competitive silica-containing organic artificial SEIs, such as silicates 24,25 , polydimethylsiloxane 7,26 , silane coupling agent 27 , and some silica composites [28][29][30][31][32] , show great potential for stabilizing LMAs with desirable features, such as good mechanic strength, lithiophilicity, and air tolerance. The high-modulus character of silica-containing artificial SEI can mechanically suppress the Li dendrite growth, the distinct lithiophilicity can regulate Li + flux to smoothen Li + deposition, and air tolerance of LMAs dramatically simplify the fabrication process [33][34][35][36][37][38] .…”
mentioning
confidence: 68%
“…Meanwhile, the PDOL phase permeated in LLTO can achieve rapid ion conduction through the coupling/decoupling of O and Li + in the -CH 2 -CH 2 -O-CH 2 -Opolymer chains. 13,28 To further analyze the topochemistry of PDOL, nuclear magnetic resonance (NMR) measurements were performed (Fig. 1e).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the PDOL phase permeated in LLTO can achieve rapid ion conduction through the coupling/decoupling of O and Li + in the –CH 2 –CH 2 –O–CH 2 –O– polymer chains. 13,28…”
Section: Resultsmentioning
confidence: 99%